MCM-41-supported platinum carbonyl cluster-derived asymmetric hydrogenation catalyst - Basu, Susmit; Paul, Himadri; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Journal of Catalysis, 2005)
Anionic platinum carbonyl cluster has been ion paired with cinchonidium groups that are chemically bound to the surface of MCM-41 and fumed silica. In the hydrogenation of methyl pyruvate or acetophenone the fumed silica-based catalyst gives zero enantioselectivity, but under optimum conditions enantiomeric excesses of >90 and similar to40%, respectively, are obtained with the MCM-41-based catalyst. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: asymmetric catalysis; functionalized inorganic oxides; hydrogenation catalysts; platinum carbonyl cluster